Simultaneous quantification of ginsenoside Rg1 and its metabolites by HPLC-MS/MS: Rg1 excretion in rat bile, urine and feces - Chiyu He; Ru Feng; Yupeng Sun; Shifeng Chu; Ji Chen; Chao Ma; Jie Fu; Zhenxiong Zhao; Min Huang; Jiawen Shou; Xiaoyang Li; Yuzhu Wang; et al. (Elsevier, 2016)
Ginsenoside Rg1 (Rg1), the major effective component of ginseng, has been shown to have multiple bioactivities, but low oral bioavailability. The aim of this study was to develop a simple, sensitive and rapid high performance liquid chromatography-tandem mass spectrometry (LC-MS/MS) method, which could be used to validate and quantify the concentrations of Rg1 and its metabolites in Sprague-Dawley rat bile, urine, and feces after oral administration (25 mg/kg). Calibration curves offered satisfactory linearity (r>0.995) within the determined ranges. Both intra-day and inter-day variances were less than 15%, and the accuracy was within 80-120%. The excretion recoveries of Rg1, ginsenoside Rh1 (Rh1), and protopanaxatriol (Ppt) in bile, urine, and feces combined were all greater than 70%. The fecal excretion recoveries of Rg1, Rh1, and Ppt were 40.11%, 22.19%, and 22.88%, respectively, whereas 6.88% of Rg1 and 0.09% of Rh1 were excreted in bile. Urinary excretion accounted for only 0.04% of Rg1. In conclusion, the observed excretion profiles for Rg1 and its metabolites after oral administration are helpful for understanding the poor oral bioavailability of Rg1 and will aid further investigations of Rg1 as a pharmacologically active component.